FORMATION OF INNOVATION ENVIRONMENT AS NECESSARY TERM OF THE REGION DEVELOPMENT - E. I. Marukovich; O. O. Stanulenis; E. M. Patuk (Литьë и металлургия, 2005)
The comparative analysis of the main social-economical and ecological indices of Mogilev region with the other regions is given in the article. The acting and perspective mechanisms of creation of favorable innovation environment are described.